An arbitrable multi‐replica data auditing scheme based on smart contracts. (13th July 2022) - Tian, Junfeng; Yang, Qian
Summary: In order to improve the availability and persistence of data, lightweight cloud users want to store multiple‐replicas of the original file on the server with less local computing and storage overhead. Meanwhile, to ensure the integrity of the remote storage data, some schemes have been designed to allow public verification. However, most existing schemes only focus on malicious cloud service providers and ignore the possibility that dishonest users cheat for profit. This article implements an arbitrable data auditing scheme under multi‐replica storage. The scheme adopts a new arbitration mechanism under multi‐replica storage, makes use of the non‐tampering characteristics of smart contracts, carries out reliable verification through miners, and realizes the timely detection and punishment of any fraudulent entity. In addition, the scheme also designs a multi‐replica storage model based on the B* tree, realizes the batch verification of replica blocks, enables the fraud behavior of malicious users to be identified after data update, and improves the space utilization efficiency. The article also gives detailed security proof of the proposed scheme. The evaluation result shows our scheme not only realizes a more practical and fairer audit scheme but also has lower computational overhead than current state‐of‐the‐art multi‐replica arbitrable schemes.